Learning Under Persistent Market Volatility: A Conceptual Model of Organizational Learning Cycles and Strategic Renewal - Tatiek Ekawati Permana (UDEX Institute, 2025)
Persistent market volatility has become a structural feature of contemporary competitive environments, yet its relationship with strategic adaptation remains theoretically under-specified. While prior research emphasizes dynamic capabilities, resilience, and structural reconfiguration, comparatively less attention has been devoted to the learning processes that mediate between sustained ambiguity and strategic renewal. This article reconceptualizes volatility not as an automatic trigger of adaptation, but as a generator of learning pressure arising from recurring interpretive discrepancies. Integrating organizational learning theory with strategic renewal scholarship, the paper develops a process model in which adaptation unfolds through recursive cycles of strategic sensemaking, experience codification, deliberate unlearning, and adaptive renewal. The model further identifies learning velocity, memory rigidity, and feedback architecture as critical moderating conditions shaping renewal outcomes. By specifying the micro-processes through which volatility-induced ambiguity is translated into calibrated strategic realignment, the framework extends organizational learning theory into persistently turbulent contexts and provides a process-based articulation of adaptive renewal under sustained market uncertainty.